The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s00384-015-2129-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the intestinal blood flow near the rectosigmoid junction using the indocyanine green fluorescence method in a colorectal cancer surgery

Abstract: This study proves that cases without the anastomosis of the marginal artery of the rectosigmoid junction truly exist, using studies in living humans (UMIN000011186).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 32 publications
0
48
0
3
Order By: Relevance
“…In a study of cadavers, Tonder et al [31] reported that there was no anastomosis in 4.7 % (3/64) at a marginal artery level between the last sigmoid arterial branch and superior rectal artery. Watanabe et al [32] also reported that the anastomosis of the marginal artery around the rectosigmoid junction was absent in 5 % ( [14]. In that study, cases with protective diverting ileostomy were excluded, and ICG fluorescence imaging was not introduced during surgery.…”
Section: Discussionmentioning
confidence: 93%
“…In a study of cadavers, Tonder et al [31] reported that there was no anastomosis in 4.7 % (3/64) at a marginal artery level between the last sigmoid arterial branch and superior rectal artery. Watanabe et al [32] also reported that the anastomosis of the marginal artery around the rectosigmoid junction was absent in 5 % ( [14]. In that study, cases with protective diverting ileostomy were excluded, and ICG fluorescence imaging was not introduced during surgery.…”
Section: Discussionmentioning
confidence: 93%
“…2 While some research groups have investigated its use as a far-red fluorophore, 29 the low fluorescence yield and lack of any functional groups for addition of ligands have limited its use in clinical applications. ICG is the only approved fluorophore in the NIR-window and several imagers have been designed and commercially launched to allow ICG guidance in surgery for blood flow assessment, [30][31][32] hepatic function assessment, 33,34 and vessel patency and perfusion evaluation especially in reconstructive 35,36 and bypass surgeries. 37,38 The low tissue autofluorescence in the NIR-wavelengths further simplifies the task of filtering out background signals, and since ICG is the primary reimbursable agent today, almost all imaging device companies have built systems specifically for ICG imaging.…”
Section: Introductionmentioning
confidence: 99%
“…В настоящий момент мы можем обобщить опуб-ликованные результаты 8 серий клинических наблю-дений (от 3 до 119 пациентов) [23, [26][27][28][29][30][31][32], 3 контроли-руемых исследований [33-35] и 1 проспективного мультицентрового исследования [36]. Частота возник-новения несостоятельности первичного анастомоза варьирует в различных исследованиях и может дости-гать 20 % [5][6][7].…”
Section: результатыunclassified